Leveraging local knowledge and satellite data for highly accurate tree-crops mapping - Reymondin, Louis (2023)
As the global community intensifies efforts to combat deforestation, meet net-zero carbon goals, and adhere to stringent certification standards, agro-industries find themselves under increasing pressure to demonstrate sustainable practices. The European Union Deforestation-Free Regulation (EUDR) adds an additional layer of scrutiny, necessitating a strategic approach to address environmental concerns. In response to this industry-driven need, our presentation at the Carbon Lab Summit showcased two groundbreaking innovations that leverage a combination of local knowledge and satellite data to create highly accurate tree-crop specific maps.